Sejmiki ziemi nurskiej 1780–1786 - Filipczak, Witold (Przegląd Nauk Historycznych, 2014)
The article concerns the sejmiks held in the land of Nur, which was a part of the Mazovian palatinate. The szlachta who arrived in the city of Nur elected envoys, deputies in the Crown Tribunal, candidates for the judiciary offices in the land of Nur, and found solutions to problems connected with self-government. Even though Mazovia was dominated by the royalist party, the sejmiks in Nur were very turbulent. In 1782 two elections connected with two offices were held simultaneously, which was against the law and thus gave rise to displeasure. The animosities between local szlachta activists made Stanisław August refrain from appointing people to some important offices in the land. The election of envoys for the sejm of 1786 was particularly tumultuous. The article includes an analysis of instructions for the representatives of the land of Nur in Parliament. It also dwells on the local political élites.